2016
DOI: 10.1016/j.bbamcr.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Proofreading of substrate structure by the Twin-Arginine Translocase is highly dependent on substrate conformational flexibility but surprisingly tolerant of surface charge and hydrophobicity changes

Abstract: The Tat system transports folded proteins across the bacterial plasma membrane, and in Escherichia coli preferentially transports correctly-folded proteins. Little is known of the mechanism by which Tat proofreads a substrate's conformational state, and in this study we have addressed this question using a heterologous single-chain variable fragment (scFv) with a defined structure. We introduced mutations to surface residues while leaving the folded structure intact, and also tested the importance of conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…It has been reported that the length of the unstructured FG repeat polypeptide dramatically affects Tat export, with longer regions abolishing Tat export altogether ( 17 ). Conversely, Jones et al ( 18 ) recently reported that the Tat system was surprisingly tolerant of hydrophobic patches on the surface of structured single-chain variable fragment proteins, and export efficiency was increased with greater structural rigidity. Chaperones may also prevent export of a protein until cofactor insertion has taken place ( 19 21 ), and mutants incapable of cofactor binding are rapidly degraded once in contact with the Tat machinery ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the length of the unstructured FG repeat polypeptide dramatically affects Tat export, with longer regions abolishing Tat export altogether ( 17 ). Conversely, Jones et al ( 18 ) recently reported that the Tat system was surprisingly tolerant of hydrophobic patches on the surface of structured single-chain variable fragment proteins, and export efficiency was increased with greater structural rigidity. Chaperones may also prevent export of a protein until cofactor insertion has taken place ( 19 21 ), and mutants incapable of cofactor binding are rapidly degraded once in contact with the Tat machinery ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three periplasmic extraction methods, cold-osmotic shock, cold-osmotic shock with MgCl 2 and EDTA/lysozyme/cold-osmotic [30]; and two cell disruption techniques, sonication [30] and freezethaw cycles, were compared in combinations to assess fraction purity (Table4). Protein localization and cross-contamination was monitored by Western blot of overexpressed proteins and selected markers.…”
Section: Resultsmentioning
confidence: 99%
“…The periplasm was extracted by EDTA/lysozyme/cold osmotic shock and the cells were lysed by sonication as described previously [30]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Requirements for conformational stability were studied using non-native Tat substrates, like PhoA and antibody fragments. These are only exported in oxidising conditions where disulphide bonds form (38,148,149,152). Nevertheless, human growth hormone (hGH) and interferon α2b are also exported via Tat without disulphide bonds formed (143), suggesting that they assume near-native states as shown for E. coli CueO, which is exported without its copper cofactor bound (144).…”
Section: Tat Proofreadingmentioning
confidence: 99%